2019
DOI: 10.1038/s41588-019-0480-1
|View full text |Cite
|
Sign up to set email alerts
|

A reference genome for pea provides insight into legume genome evolution

Abstract: ea (Pisum sativum L., 2n = 14) is the second most important grain legume in the world after common bean and is an important green vegetable with 14.3 t of dry pea and 19.9 t of green pea produced in 2016 (http://www.fao.org/faostat/). Pea belongs to the Leguminosae (or Fabaceae), which includes cool season grain legumes from the Galegoid clade, such as pea, lentil (Lens culinaris Medik.), chickpea (Cicer arietinum L.), faba bean (Vicia faba L.) and tropical grain legumes from the Milletoid clade, such as commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
496
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 423 publications
(595 citation statements)
references
References 106 publications
20
496
0
1
Order By: Relevance
“…There is of course a certain amount of reorganization that can be easily observed, for example, in the condensed LGI of faba bean that gathers the genes located on chromosomes 1, 2 and 5 of pea. These results include V. faba as an additional syntenic species in the paleogenomic scheme described in Kreplak et al 48 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…There is of course a certain amount of reorganization that can be easily observed, for example, in the condensed LGI of faba bean that gathers the genes located on chromosomes 1, 2 and 5 of pea. These results include V. faba as an additional syntenic species in the paleogenomic scheme described in Kreplak et al 48 .…”
Section: Discussionsupporting
confidence: 59%
“…By contrast, the number of markers in our consensus map may not be enough to clarify the macrosynteny between faba bean and soybean due to the extensive chromosomal rearrangements and polyploidization of the soybean genome. Hopefully, gene conservation with soybean will be more evident once the faba bean genome is available, as has happened in the case of the pea 48 . Although duplication of the soybean genome and chromosomal rearrangement are a limitation for translational genomics with faba bean, synteny in duplicate regions would be a good resource to exploit.…”
Section: Discussionmentioning
confidence: 99%
“…3) mostly agrees with expectations from the point of view of morphology and taxonomy; that is evolution of a single gene chosen for its high variability (Zaytseva et al, 2012) appears to have been in line with the mainstream pea evolution, more or less reflected in its taxonomy. The principal topology of the phylogenetic trees reconstructed by Kreplak et al (2019: Fig. 6) on the basis of 2 thousand nuclear SNP is the same as in our tree based on a single nuclear gene (Fig.…”
Section: Role Of Nuclear-cytoplasmic Incompatibility In Shaping Organmentioning
confidence: 85%
“…sativum.Phylogenetic analyses of various pea taxa with molecular markers indicate that hybridization between wild peas is not an extensive phenomenon [8]. The recently annotated pea genome sequence and the resequencing of data from 42 wild, landrace and cultivar Pisum genotypes, provided further insights into legume genome evolution [9]. It has been suggested that the common ancestor of the Pisum species was probably cytogenetically similar to P. sativum subsp.…”
mentioning
confidence: 99%
“…elatius ancestor [10] followed by a migration to Abyssinia, possibly through ancient human trading routes [11], indicating at least two domestication events independent of P. sativum subsp. sativum [9,12]. The alternative hypothesis about the origins of P. abyssinicum suggests that it derived from a hybridization event between P. fulvum and P. sativum subsp.…”
mentioning
confidence: 99%